2019
DOI: 10.1128/jvi.00138-19
|View full text |Cite
|
Sign up to set email alerts
|

The N Terminus of Human Cytomegalovirus Glycoprotein O Is Important for Binding to the Cellular Receptor PDGFRα

Abstract: The human cytomegalovirus (HCMV) glycoprotein complex gH/gL/gO is required for the infection of cells by cell-free virions. It was recently shown that entry into fibroblasts depends on the interaction of gO with the platelet-derived growth factor receptor alpha (PDGFR␣). This interaction can be blocked with soluble PDGFR␣-Fc, which binds to HCMV virions and inhibits entry. The aim of this study was to identify parts of gO that contribute to PDGFR␣ binding. In a systematic mutational approach, we targeted poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 66 publications
4
28
0
Order By: Relevance
“…Although this peptide site overlaps with the recombination site of GT1c/GT3, the specific sequence remained unchanged upon recombination suggesting that sPDGFRα binding to this recombinant form of gO is not impaired. This presumption fits well to the finding that gO GT1c/GT3 mutant does not display a phenotype in fibroblast infectivity while mutants with a mutation in this particular peptide sequence showed reduced penetration into fibroblasts (31). Hence, we assume that the impaired sPDGFRα inhibition for gO GT1c/GT3 mutant on epithelial cells is not caused by a lower binding of sPDGFRα to gO but rather by an impaired interference with a downstream entry step mediated by the trimer.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Although this peptide site overlaps with the recombination site of GT1c/GT3, the specific sequence remained unchanged upon recombination suggesting that sPDGFRα binding to this recombinant form of gO is not impaired. This presumption fits well to the finding that gO GT1c/GT3 mutant does not display a phenotype in fibroblast infectivity while mutants with a mutation in this particular peptide sequence showed reduced penetration into fibroblasts (31). Hence, we assume that the impaired sPDGFRα inhibition for gO GT1c/GT3 mutant on epithelial cells is not caused by a lower binding of sPDGFRα to gO but rather by an impaired interference with a downstream entry step mediated by the trimer.…”
Section: Discussionsupporting
confidence: 85%
“…Remarkably, one of the two recombinant mutants, gO GT1c/GT3, displayed a significantly lower sensitivity for sPDGFRα inhibition on epithelial cells than the other mutants while the fibroblast inhibition was similarly effective. As mentioned above this mutant comprises its recombination site in the highly polymorphic N-terminal region of the protein, which only recently was suggested to contain the PDGFRα receptor binding domain (31). By mutational analysis the authors identified a small stretch from amino acid 117 to 121 causing the strongest impairment of sPDGFRα binding to virus particles and consequently also a reduced virus penetration into fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to HCMV gO, GP74 protein (22122 strain) is heavily glycosylated with 13 predicted sites [ 15 ]. In the TAMYC strain, the first two predicted N-glycosylation sites (N-X-T/A) are lost (amino acids 41 and 57) [ 15 ] ( Figure 1 ) and the potential impact of this loss in this N-terminal domain glycosylation awaits further study but the second glycosylation site is conserved between HCMV and GPCMV gO [ 42 ]. Potentially modified glycosylation could impact on ability of gO to interact with PDGFRA cell receptor [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…This concern is partially alleviated by the observation that the engineered PDGFRα mutants maintain high binding to soluble HCMV trimer from the Merlin clinical strain [58] ( Fig 3C), which has relatively high natural sequence variation compared to TB40/E (79% identity between glycoproteins O). Variation is particularly high in the N-terminus of glycoprotein O where important interactions to PDGFRα reside [54].…”
Section: Surface Mutations At the Pdgf Binding Site Favor Pdgfrα Specmentioning
confidence: 99%